The role of de novo variants in patients with congenital diaphragmatic hernia - Bendixen, Charlotte; Reutter, Heiko Martin (Genes, 2021)
The genetic etiology of congenital diaphragmatic hernia (CDH), a common and severe birth defect, is still incompletely understood. Chromosomal aneuploidies, copy number variations (CNVs), and variants in a large panel of CDH-associated genes, both de novo and inherited, have been described. Due to impaired reproductive fitness, especially of syndromic CDH patients, and still significant mortality rates, the contribution of de novo variants to the genetic background of CDH is assumed to be high. This assumption is supported by the relatively low recurrence rate among siblings. Advantages in high-throughput genome-wide genotyping and sequencing methods have recently facilitated the detection of de novo variants in CDH. This review gives an overview of the known de novo disease-causing variants in CDH patients.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Congenital diaphragmatic hernia; De novo variants; Impaired reproductive fitness; Mortality